Bentuk Apologetika Terhadap Hyper-Grace Berdasarkan Titus 2:11-15 - Joseph Patalala; Tumpal Pandiangan; Yugiantie Solaiman (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
Biblically, the Hyper-Grace adherents mistake their analysis of very basic doctrines. The author sees first, an indication of Hyper-Grace's understanding which states that when we are saved, God has already forgiven all of our sins, namely past, present, and future sins, so that they are principled if there is a sin that we commit, there is no need to ask. forgiveness to the Lord Jesus. Second, there is an indication of understanding the concept of salvation once saved remains saved, which is understood as a certainty of salvation without needing to work out that salvation through a holy life, fearing God. Third, there are indications that ecclesiastical problems do not understand the biblical concept of salvation in Jesus Christ, so they are very easy to follow the teachings of the concept of salvation which is not necessarily according to the Bible. From the description of the limitations of the problem under study, the authors ask 3 (three) main questions regarding the discussion of this scientific paper. First, what are the things related to Hyper-Grace? This will explain aspects in terms of understanding Hyper-Grace. Second, how to approach the exegesis of Titus 2: 11-15 as a response or evaluation of the Hyper-Grace movement? Third, Is it once saved, can't you lose your salvation (Once Saved Forever)? The purpose of the research being held is to answer every problem that has been mentioned above, the author hopes that every Christian has a correct basis for understanding the biblical concept of salvation. The author hopes to contribute in terms of thought, so that every Christian can apologize to deviant teachings, namely Hyper-Grace is not in accordance with Biblical Grace. The author hopes to know the Biblical view by examining Titus 2: 11-15 as the basis of the author's analysis of Apologetics. The purpose of this analysis is also an evaluation of the Hyper-Grace movement which is widely debated by biblical scholars. Secara biblika, penganut Hyper-Grace memiliki kekeliruan terhadap analisanya kepada doktrin-doktrin yang sangat mendasar. Penulis melihat pertama, adanya indikasi pemahaman Hyper-Grace yang menyatakan bahwa pada saat kita diselamatkan, Tuhan sudah mengampuni semua dosa kita yaitu dosa masa lalu, masa kini, dan masa yang akan datang, sehingga mereka berprinsip seandainya ada dosa yang kita lakukan tidak perlu lagi meminta pengampunan kepada Tuhan Yesus. Kedua, adanya indikasi pemahaman konsep keselamatan sekali selamat tetap selamat, yang dipahami sebagai satu kepastian keselamatan tanpa perlu mengerjakan keselamatan itu melalui kehidupan yang kudus, takut akan Tuhan. Ketiga, adanya indikasi masalah gerejawi tidak memahami konsep keselamatan Alkitabiah didalam Yesus kristus, sehingga mereka sangat mudah mengikuti ajaran konsep keselamatan yang belum tentu sesuai Alkitab. Dari pemaparan batasan masalah yang diteliti tersebut, maka penulis mengajukan 3 (tiga) pertanyaan utama mengenai pembahasan karya ilmiah ini. Pertama, apa saja hal-hal yang berkaitan dengan Hyper-Grace? Hal ini akan menjelaskan aspek-aspek yang ditinjau dari pemahaman Hyper-Grace. Kedua, Bagaimana pendekatan eksegesis Titus 2:11-15 sebagai respon atau evaluasi terhadap gerakan Hyper-Grace? Ketiga, Apakah sekali diselamatkan, tidak bisa kehilangan keselamatan (Once Saved Forever)? Tujuan penelitian diadakan adalah untuk menjawab setiap permasalahan yang telah disebutkan diatas, penulis berharap agar setiap orang Kristen memiliki dasar yang benar akan pemahaman tentang konsep keselamatan yang Alkitabiah. Penulis berharap dapat memberi kontribusi dalam hal pemikiran, agar setiap orang Kristen dapat berapologetika terhadap pengajaran yang menyimpang yaitu Hyper-Grace tidak sesuai dengan Grace Alkitabiah. Penulis berharap untuk mengetahui pandangan Alkitabiah dengan mengkaji Titus 2:11-15 sebagai dasar Apologetika analisis penulis. Tujuan dari analisis ini juga sebagai evaluasi terhadap gerakan Hyper-Grace yang banyak diperdebatkan oleh para sarjana Alkitab.